Souvenirs rétrospectifs de l’Anthropocène : la ville dans la cli‑fi italienne - Lucia Della Fontana (ReS Futurae)
By bringing the "unthinkable" into our daily lives, global climate change blurs the boundaries between reality and fiction. Since the beginning of the century, the urgency of environmental awareness has marked a turning point in the Western philosophical and aesthetic landscape. In order to rethink our cognitive and affective structures, from the 2000s onwards, many writers have moved away from realism to adopt estranging devices. This is where cli‑fi, the new genre theorised by Daniel Bloom, comes into play. In order to represent climate change, cli‑fi reactivates dystopian and apocalyptic schemes and sets up a narrative twist that consists in presenting the coming catastrophe as if it had already happened. The reader is thus led to apprehend what is coming through the retrospective modality of the future perfect. At the same time, the narration of the ecological crisis displaces non-human agencies to the foreground, inverting the relationship between figure and background. Thus, in Italian cli‑fi, the city imposes itself as a real protagonist. By staging a porous continuity between the body of the city and that of its inhabitants, Italian cli-fi attempts to imagine the world to come on the basis of what Roberto Esposito has called the "immunization paradigm". Polarized by the fear of invasion and the need to survive by opening to others, these stories hesitate between utopian tension and resignation.